(untitled) (Circe de clásicos y modernos, 2018)
The speeches by Ajax and Odysseus, whose authorship is ascribed to the Socratic philosopher Antisthenes, give us the chance to trace some pos-sible connections between philosophy, sophistic and poetry. In the bases of these connections we can find an important element present in Antisthenes’ conception of language: the notion of χρῆσις τῶν ὀνομάτων (use of names). We are going to examine how some scenes from the epic tradition, together with some rhetorical strategies, are seen through a conception of language in which the meaning of a word depends on the social and historical conditions in which that term is used.